Oversight Issues in Mobile Payments - Khiaonarong, Tanai (IMF Working Papers; Working Paper, 2014)
This paper examines oversight issues that underlie the potential growth and risks in mobile payments. International experience suggests that financial authorities can develop effective oversight frameworks for new payment methods to safeguard public confidence and financial stability by establishing: (i) a clear legal regime; (ii) proportionate AML/CFT measures to prevent financial integrity risks; (iii) fund safeguarding measures such as insurance, similar guarantee schemes, or 'pass through' deposit insurance; (iv) contingency plans for operational disruptions; and (v) risk controls and access criteria in payment systems. Such measures are particularly important for low-income countries where diffusion is becoming more widespread.